Laminoplasty for the treatment of extramedullary intradural tumors in the thoracic and lumbar spine: greater than two‐year follow‐up - Liu, Xin‐yu (Orthop Surg, 2009)
Objective:  To investigate the outcome of a laminoplasty technique without additional instrumentation for fixation of laminae in the treatment of extramedullary intradural tumors in the thoracic and lumbar spine. Methods:  Twenty‐four patients (15 men and 9 women) with extramedullary intradural tumors in the thoracic and lumbar spine were included in our study. The average age was 36.2 years (range 18 to 61 years). The pathological diagnosis was neurofibroma in 13, ependymoma in 6, lipoma in 2 and teratoma in 3 cases. All patients underwent the same laminoplasty surgery as follows: the laminae were reattached to their original sites, the ligaments (including the supraspinal, interspinal and yellow ligaments) were conserved, and primary stability of the re‐attached laminae was achieved with silk or nylon sutures. Results:  Sixty‐six laminae were re‐implanted in 24 patients. The average length of follow‐up was 34.2 months (26.5 to 41 months). Fusion of the laminae was achieved in a mean of 4.5 months (3 to 6 months). Unilateral healing of the incision lines was observed in seven cases, including one with two‐level laminotomy, three with three‐level laminotomy and three with four‐level laminotomy. The other 17 cases underwent bilateral fusion. Conclusion:  Fixing the laminae, spinous processes and ligaments with sutures can achieve satisfactory primary stability and high fusion rates for resected laminae. Additional instrumentation may be necessary in greater than three‐level laminoplasty.